Comparison of Training Qualifications Programs, for Operating Boats and Yachts, which are not Covered by STCW Convention in the United Kingdom and the Republic of Croatia - Darijo Mišković; Đani Mohović; Igor Rudan (Naše More (Dubrovnik), 2017)
Research in this paper was conducted under the EU project TRECVET Core Curriculum for Skippers of Small Commercial Vessels (in short TCC-SCV) where a Faculty of Maritime Studies Rijeka was a project partner. The goal of the project was to analyze seven professional SCV skipper qualifications from UK, France, Spain, Germany, Slovenia, Czech Republic and Croatia by breaking them into their smallest parts called Fundamental Elements and thereby offering objective comparability. After reviewing and comparing training programs in The United Kingdom and The Republic of Croatia for qualifications, required for operating boats and yachts, set by the appropriate Authorities, this paper analyzed skipper/yacht master certification scheme in terms of theoretical education and practical trainings, syllabus contents, required experience, examination methods and evaluated the overall characteristics. At the end, the authors pointed out to some deficiencies in current training program in The Republic of Croatia and drew the conclusion that experience and lessons from other training programs can find purpose for training program reform in their own country.